Temporomandibular joint ankylosis in a child: an unusual case with delayed surgical intervention. Issue 1 (December 2015) - Yew, Ching; Rahman, Shaifulizan; Alam, Mohammad
Abstract Background The Temporomandibular Joint (TMJ) ankylosis in child is rare and yet the causes still remain unclear. This condition that affects the feeding and possible airway obstruction do not only worry the parents, but also possesses as a great challenge to the surgeons. Furthermore, it interferes with the facial skeletal and dento-alveolar development in the on growing child. Case presentation In this case report, we presented the management of a 7 year old with left TMJ ankylosis discovered since infant. Clinical and imaging investigations were consistent with left temporomandibular joint ankylosis (Type IV) possible secondary to childhood septic arthritis. Left gap arthroplasty via modified Al Kayat Bramley and retromandibular approach was performed, with interpositional arthroplasty placement of temporalis fascia graft. No complications from the surgery except reduced mouth opening were seen. Possible contributing factors to this less than satisfactory mouth opening are adressed. Conclusion We describe here, an unusual childhood temporomandibular joint ankylosis possible due to septic arthritis with delayed surgical intervention. The aetiology, classifications, timing and choice of surgical techniques along with its considerations and complications are discussed. Although there is no consensus on the surgical treatment of TMJ ankylosis, early mobilisation, aggressive physiotherapy and close follow-up are advocated by many authors for successful treatment.